2021
DOI: 10.3390/cancers13153808
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Primary Motor Cortex (M1) Functional Components in M1 Gliomas Enhances Safe Resection and Reveals M1 Plasticity Potentials

Abstract: Primary-Motor-Cortex (M1) hosts two functional components, at its posterior and anterior borders, being the first faster and more excitable. We developed a mapping-technique for M1 components identification and determined their functional cortical-subcortical architecture in M1 gliomas and the impact of their identification on tumor resection and motor performance. A novel advanced mapping technique was used in 102 tumors within M1 or CorticoSpinal-Tract to identify M1-two components. High-Frequency-stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…В то же время существуют рекомендации, апеллирующие к повышенному риску развития судорожных приступов при низкочастотной стимуляции и советующие применять во всех случаях параметры М. Taniguchi [12]. Кроме того, возможно переключение этих параметров при кортикальной и субкортикальной стимуляции [13,14].…”
Section: Discussionunclassified
“…В то же время существуют рекомендации, апеллирующие к повышенному риску развития судорожных приступов при низкочастотной стимуляции и советующие применять во всех случаях параметры М. Taniguchi [12]. Кроме того, возможно переключение этих параметров при кортикальной и субкортикальной стимуляции [13,14].…”
Section: Discussionunclassified
“…Traditionally, high-frequency monopolar stimulation is administered as a monophasic wave pulse in trains of 5 (0.5 ms pulse duration, 1–4 ms interstimulation interval, 0–20 mA); however, more recently, reduced trains of 1 to 2 [ 51 , 66 ] have demonstrated added utility as well. Rossi et al directly compared these two protocols and identified tumor subgroups in which shorter trains may offer additional insight.…”
Section: Nuances Of Intraoperative Motor Mapping Techniques and Measu...mentioning
confidence: 99%
“…Rossi et al directly compared these two protocols and identified tumor subgroups in which shorter trains may offer additional insight. In tumors outside of the primary motor cortex and cortical spinal tracts, those only affecting the cortical spinal tracts, or those originating within the primary motor cortex with normal cortical architecture, ‘train of 2’ stimulation better segregated the anterior and posterior regions of the primary motor cortex—a distinction that may aid in maximizing EOR while preserving long-term function [ 66 ]. In addition, only the two trains of stimulation identified function-free zones in primary motor cortex tumors with distorted cortical architecture.…”
Section: Nuances Of Intraoperative Motor Mapping Techniques and Measu...mentioning
confidence: 99%
“…This enables the surgeon to adjust the speed of resection when approaching the corticospinal tract [135,137]. Rossi et al developed an advanced mapping technique used for tumors located within the primary motor cortex or subcortical motor pathways [138]. They used high-frequency stimulation (HF-To5 and HF-To2) in the exposed motor cortex in order to establish the safe entry zone for the corticectomy [138].…”
Section: Brain Mapping Monitoring Strategies and Awake Surgery: Locat...mentioning
confidence: 99%